Coronavirus Disease-19: Disease Severity and Outcomes of Solid Organ Transplant Recipients: Different Spectrums of Disease in Different Populations?. Issue 1 (24th August 2020) - Ali, Tariq; Al-Ali, Ali; Fajji, Layal; Hammad, Ehab; Nazmi, Ahmed; Alahmadi, Ibrahim; Aleid, Hassan; Ullah, Asad; Shah, Yaser; Broering, Dieter
Abstract : Background: Coronavirus disease-19 (COVID-19) is associated with significant mortality. The elderly, patients with comorbidities, and solid organ transplant (SOT) recipients are particularly at risk. We observed a low incidence of severe disease in our population and aimed to determine the outcomes of COVID-19 (disease severity/intensive care unit [ICU] admissions/mortality) in SOT recipients. Methods: All SOT recipients diagnosed with COVID-19 were included. Their demographic and clinical data were recorded from the hospital electronic system. Patients were assigned to 1 of 4 stages of disease severity: stage A = asymptomatic, stage B = mild, stage C = moderate, and stage D = severe. Results: Of the 3052 SOT recipients, 67 were diagnosed with COVID-19. The mean age was 52 years, and 69% were male. There were approximately 25% patients in stage A, 28% in stage B, 34% in stage C, and 12% in stage D. Patients in stages C and D were older than those in stage A ( P = 0.04) or stage B ( P = 0.03). Lactic dehydrogenase ( P < 0.01) and D-dimer ( P < 0.01) levels were higher across the stages. Approximately 70% of patients were admitted for a median duration of 9 days and the median follow-up was 35 days. Acute kidney injury occurred in 19% of patients, and 45% required supplementary oxygen. The symptomatic patients were treated with Hydroxychloroquine (83%), Azithromycin (89%), and Tocilizumab (23%). Around 15% of patients were admitted to ICU and 2 patients have died. Conclusions: Most SOT recipients developed mild to moderate COVID-19 infection; few required ICU admission and 2 patients have died. Remaining patients have recovered and have been discharged from the hospital.